Strain engineering a multiferroic monodomain in thin-film BiFeO3: Data archive - Price, N (University of Oxford, 2019)
Data used to generate the figures in the article titled "Strain engineering a multiferroic monodomain in thin-film BiFeO3: Data archive" in Physical Review Applied. Please see DOI TO BE INSERTED for further details.